2012
DOI: 10.21829/myb.2012.183357
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización de hojas de mazorca de maíz y de bagazo de caña para la elaboración de una pulpa celulósica mixta

Abstract: En este artículo se presentan los resultados obtenidos en la caracterización química y morfológicade las hojas de mazorca de maíz (Zea mays) y del bagazo de caña (Saccharum officinarum L.).Se analizaron porcentajes de α-celulosa, holocelulosa, lignina y cenizas, según las Normas Tappi paracada componente y el método de Jayme-Wise. Se determinaron las propiedades biométricas de lasfibras de cada planta (longitud y diámetro, grosor de la pared y diámetro del lumen). Además, se estimaronlos índices de calidad de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 1 publication
0
8
0
8
Order By: Relevance
“…In the butanolic fractions of the extract used in this study, it was possible to identify cellulose and lignin using NMR (spectra not shown in this paper). Corn husks contain mainly cellulose, hemicellulose, lignin and smaller amounts of several soluble carbohydrates [5]. The use of cellulose-like reducing agents has been reported for the synthesis of AgNPs [6]; lignin has been used to obtain nanostructures due to its OH groups [7], and hemicellulose has been reported for AgNP stabilization [8].…”
Section: Resultsmentioning
confidence: 99%
“…In the butanolic fractions of the extract used in this study, it was possible to identify cellulose and lignin using NMR (spectra not shown in this paper). Corn husks contain mainly cellulose, hemicellulose, lignin and smaller amounts of several soluble carbohydrates [5]. The use of cellulose-like reducing agents has been reported for the synthesis of AgNPs [6]; lignin has been used to obtain nanostructures due to its OH groups [7], and hemicellulose has been reported for AgNP stabilization [8].…”
Section: Resultsmentioning
confidence: 99%
“…De acuerdo, con distintos autores [11], la biomasa residual del cultivo del maíz (cañas, hojas, tuzas varía entre 20 a 35 ton/ha en maíz blanco y de 16 a 25 ton/ha en maíz amarillo y aproximadamente 1 ton/ha de mazorcas sin maíz. Por tanto, se esperaría en promedio 9 millones de ton/corte de residuos por la siembra de maíz blanco en Colombia.…”
Section: Resultsunclassified
“…The bagasse tissue has a cellular structure composed of medulla, mainly formed of parenchymal cells of thin, elastic walls and numerous perforations. Besides being associated with fibrovascular bundles, which are thin, thin-walled with blunt ends, forks and their surfaces occasionally have small pores [21]. On the other hand, the bark fibers lignified, with higher length, diameter and thicker walls and pores present in the entire surface [22] [23].…”
Section: Discoloration Of Azo Compoundmentioning
confidence: 99%